Flagellar Motility Is a Key Determinant of the Magnitude of the Inflammasome Response to Pseudomonas aeruginosa - Patankar, Yash R. (American Society for Microbiology, 2013)
We previously demonstrated that bacterial flagellar motility is a fundamental mechanism by which host phagocytes bind and ingest bacteria. Correspondingly, loss of bacterial motility, consistently observed in clinical isolates from chronic Pseudomonas aeruginosa infections, enables bacteria to evade association and ingestion of P. aeruginosa by phagocytes both in vitro and in vivo. Since bacterial interactions with the phagocyte cell surface are required for type three secretion system-dependent NLRC4 inflammasome activation by P. aeruginosa, we hypothesized that reduced bacterial association with phagocytes due to loss of bacterial motility, independent of flagellar expression, will lead to reduced inflammasome activation. Here we report that inflammasome activation is reduced in response to nonmotile P. aeruginosa. Nonmotile P. aeruginosa elicits reduced IL-1β production as well as caspase-1 activation by peritoneal macrophages and bone marrow-derived dendritic cells in vitro. Importantly, nonmotile P. aeruginosa also elicits reduced IL-1β levels in vivo in comparison to those elicited by wild-type P. aeruginosa. This is the first demonstration that loss of bacterial motility results in reduced inflammasome activation and antibacterial IL-1β host response. These results provide a critical insight into how the innate immune system responds to bacterial motility and, correspondingly, how pathogens have evolved mechanisms to evade the innate immune system.